Development Of Design Of Experiment Software For Two-Factor Factorial Design - Ungku Mohsin, Ungku Ahmad Zahir (Universiti Sains Malaysia, 2006)
Regarding to the title, “Development Of A Design Of Experiment (DOE) Software For the case Two-Factor Factorial Designs (FD)”, this project is intended as to develop a simple software which will be able to analyze any experiment that involving only two factors as for this kind of experiment is being used widely by an industrial sectors. Therefore, the basic knowledge of FD technique is very important to engineering students especially whom involved in many experiments as to use it in solving an analysis problem. The essential of the DOE technique have been proven in the world as in Malaysia itself, many industries have supported their analyzer and the experimenter to apply one of this DOE technique in their researches and experiments. The effect reflected by seen that the several major companies such as Motorola, Hewlett-Packet, Petronas and other companies succeeding in controlling their quality level by this DOE technique. By isolating and removing the undetected factors. Those factors interrupt the product production process of several companies such as the manufacturing company. The most considerable effect is when those factors also affecting the quality level of a product produced. Therefore, as the preparation before entering the industry world, this project wants to help engineering students learning the effectiveness of this FD technique. Besides that, this project revealing the use of computer software to engineering students in analyzing an experiment. The development of this software is being constructed with a reason for students will be able to coup the computer skills and able to analyze any experiment data fast and effectively.